A Comprehensive Computer-Aided Review of Trends in Heterogeneous Catalysis and Its Theoretical Modelling for Engineering Catalytic Activity - Gerardo Valadez Huerta; Kaoru Hisama; Michihisa Koyama (Journal of Chemical Engineering of Japan)
Writing scientific literature reviews is highly challenging, especially for broad topics like “heterogeneous catalysis” due to the explosion of knowledge. In this article, we introduce a machine-assisted approach aimed to facilitating this process. It integrates an automated summarization of several sources into the conventional method of writing a literature review. Our approach represents an initial trial to compile recent trends in heterogeneous catalysis. We chose the topic of heterogeneous catalysis due to its significance in various industrial processes and its multidisciplinary nature, which makes reviewing it challenging. The review highlights the pursuit of more advanced and complex catalysts to enhance catalytic performance. These advances significantly influence chemical reaction engineering, which combines reaction chemistry and chemical engineering. The trend of developing complex catalysts faces feasibility challenges, underscoring the importance of balancing practicality and potential benefits. In this interplay, the role of atomistic understanding becomes more important as it provides insights into the fundamental mechanisms governing catalyst behavior. Therefore, this review also covers advances in computational studies, particularly density functional theory calculations and the incorporation of new techniques. The wide scope of knowledge presented in this initial trial will facilitate further development in the field of chemical reaction engineering.